Human neuronal excitation/inhibition balance explains and predicts neurostimulation induced learning benefits - van Bueren, Nienke E. R.; van der Ven, Sanne H. G.; Hochman, Shachar; Sella, Francesco; Cohen Kadosh, Roi (PLOS Biology, 2023)
Previous work has suggested that the excitation/inhibition ratio (E/I) contributes to typical and atypical development, mental health, cognition and learning. This study reveals that the E/I ratio in the brain plays an important role in neurostimulation efficacy and is a possible marker for learning.